A Fresh Chance for Africa's Youth: Labour Market Effects of the African Continental Free Trade Area (AfCFTA) - Ioana Lungu (Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH, 2019)
The African Continental Free Trade Area marks a historic decision on the road to regional economic integration on the continent. If implemented, the agreement has the potential to make a significant impact on improving the livelihoods of the African people, by increasing intra-African trade and generating new employment opportunities on an integrated African labour market.
Keywords: J21; J24; O10; O40; F15; F16; 330; international trade; regional economic integration; Africa; development; labor market